Atmospheric Oxidation Reactions of Methyl Salicylate as Green Leaf Volatiles by OH Radical: Theoretical Kinetics and Mechanism. Issue 40 (28th October 2020) - Seif, Ahmad; Domingo, Luis Ramon; Mazarei, Elham; Zahedi, Ehsan; Ahmadi, Temer Shah
Abstract: Green leaf volatile (GLV) organic compounds, released from vegetation, act as plants' multifunctional weapon and are known to be a source of secondary organic aerosols (SOAs). In the present study, the mechanism of oxidation reaction of methyl salicylate (MeSa), a known GLV, by OH radical has been investigated by means of density functional theory (DFT). Canonical transition state (CTST) and Rice‐Ramsperger‐Kassel‐Marcus theories (RRKM) with Wigner and Eckart tunneling correction were applied to calculate the transition pressure, the total rate constant, and the individual rate constants for every channel of this oxidation reaction of MeSa with OH radical. The calculated overall bimolecular rate constant with Eckart tunneling correction for the title reaction is 1.18×10 9 and 1.01×10 9  L mol −1 s −1 at Mn15‐L/aug‐cc‐pVTZ and MN15‐L/MG3S levels of theory in the gas phase at 298 K which is comparable to the experimental reported value of 6.66×10 9  L mol −1 s −1, indicating that the results of MN15‐L/aug‐cc‐pVTZ level of theory is more accurate. Investigation of transition pressure and fall‐off curve of unimolecular channels at proposed mechanism for oxidation reaction of MeSa revealed that the TST breaks down slightly to estimate the high pressure limit of reaction rate and the reaction become second order (bimolecular reaction). Furthermore, the atmospheric lifetime of MeSa is about 2.95 and 3.44 days calculated at those two levels of theory, respectively, which indicates that MeSa can be considered as a medium‐lifetime organic volatile compound. Abstract : Pressure dependence of rate constants for unimolecular reactions at oxidation of MeSa at MN15‐L/aug‐cc‐pVTZ level of theory at 298.15 K. The value of transition pressures (P1/2 ) for unimolecular channels shows the highest value of P1/2 is related to conversion reactions of VdW2 to P3 and VdW3 to P5. The values of the transition pressures indicate that the unimolecular reaction channels do not exactly follow a first‐order rate law at atmospheric pressure.